2000
DOI: 10.1038/71582
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Plasmodium falciparum-infected erythrocytes to hyaluronic acid in placental malaria

Abstract: Infection with Plasmodium falciparum during pregnancy leads to the accumulation of parasite-infected erythrocytes in the placenta, and is associated with excess perinatal mortality, premature delivery and intrauterine growth retardation in the infant, as well as increased maternal mortality and morbidity. P. falciparum can adhere to specific receptors on host cells, an important virulence factor enabling parasites to accumulate in various organs. We report here that most P. falciparum isolates from infected pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
235
1
8

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(256 citation statements)
references
References 22 publications
10
235
1
8
Order By: Relevance
“…In previous studies that reported IRBC binding to HA, bvhHA was used for the analysis of IRBC binding. [27][28][29][30] Therefore, we also assessed the coating of bvhHA to plastic plates. As shown in Figure 1A, a low but significant amount of HA was coated onto the plastic surface; the immobilization of HA when coated with bvhHA is likely through HABPs present in samples that are adsorbed onto the plastic surface.…”
Section: Preparation and Immobilization Of Ha-bsa Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies that reported IRBC binding to HA, bvhHA was used for the analysis of IRBC binding. [27][28][29][30] Therefore, we also assessed the coating of bvhHA to plastic plates. As shown in Figure 1A, a low but significant amount of HA was coated onto the plastic surface; the immobilization of HA when coated with bvhHA is likely through HABPs present in samples that are adsorbed onto the plastic surface.…”
Section: Preparation and Immobilization Of Ha-bsa Conjugatesmentioning
confidence: 99%
“…[27][28][29][30] However, the presence of HA in human placenta at locations where IRBCs are known to adhere has not been demonstrated, and thus, it remains unclear whether HA is a receptor for placental IRBC adherence or not. If HA is indeed an additional receptor in the placenta for IRBC adherence, then this phenomenon has profound implications for the rational design of vaccine for women of child-bearing age, because a vaccine that specifically blocks the adherence of IRBC to C4S would not be sufficient to control placental infections.…”
mentioning
confidence: 99%
“…There are, however, reports pinpointing the possible role of other receptors in placental sequestration. Hyaluronic acid (HA), yet another GAG, has been reported to interact with placental isolates (15). Some isolates bind solely to HA, whereas others interact with both HA and CSA.…”
mentioning
confidence: 99%
“…The central pathophysiologic events in severe Plasmodium falciparum malaria are the inability of the host defenses to control parasite replication, cytokine imbalance resulting in the excessive release of proinflammatory cytokines in response to infection, and the sequestration of parasitized erythrocytes (PEs) 3 in the microvasculature of vital organs (2)(3)(4)(5)(6). Several receptors have been implicated in the cytoadherence of PEs to vascular endothelium, including ICAM-1 (7)(8), VCAM-1 (9 -10), E-selectin (10), platelet/endothelial cell adhesion molecule-1/CD31 (11), chondroitin-4-sulfate (12), hyaluronic acid (13), thrombospondin (TSP) (14), ␣ v ␀ 3 (15), and CD36 (16 -20).…”
mentioning
confidence: 99%